Exploring the Drivers of Greenhouse Gas Emissions in Pakistan: The Role of Deforestation, Urbanization, and Economic Growth - Ismail, Mudsir; Akhtar, Shamim; Arshad, Zeeshan; Bilal, Muddassar (International Journal of Energy Economics and Policy, 2025)
This study examines the relationship between deforestation and greenhouse gas (GHG) emissions in Pakistan, with a focus on the roles of urbanization, financial development, and economic growth. Using data from 2001 to 2023, the study employs an Autoregressive Distributed Lag (ARDL) bound testing approach to examine the short- and long-run dynamics of these variables. The results indicate that urbanization and GDP significantly increase CO2 emissions, while deforestation has a negative short-run impact with minimal long-run effects. The study emphasizes the importance of implementing effective environmental policies, including environmental taxes and market-based strategies, to reduce greenhouse gas (GHG) emissions and mitigate the ecological impacts of deforestation.